TINGKAT PENGETAHUAN TENTANG ALAT KONTRASEPSI IUD PADA AKSEPTOR KB NON IUD DI PUSKESMAS PAKEM TAHUN 2015 - Purborini, Wahyu; Theresia, Endah Marianingsih; Setiyawati, Nanik (Poltekkes Kemenkes Yogyakarta, 2016)
The usage of the IUD contraceptive in Yogyakarta has not reached the targets. Yogyakarta health profile mentions the use of the IUD in Sleman. Pakem Subdistrict is the lowest long-term usage of contraceptive IUD by the number of couples of reproductiveage (EFA) of 5600 and the number of IUD acceptors use is 1.3%. This study aims to determine the level of knowledge aboutIUD contraceptive of non IUD KB acceptors. The type of research is non-descriptive research. This research was conductedin March untilApril 2015 andislocatedin thePakemhealth centerwith research subjects allmothers who use the non KB IUDacceptors in Pakem health centerwith the characteristics of age, education level, occupation, and parity. The instrumentused is a questionnaire that has been done to test the validity beforehand. Data analysis using univariate analysis bygenerating a frequency distribution of each variable. The result of the research is that the level of knowledge aboutcontraceptive IUD from 32 research subjects is a majority (81.25%), others less knowledgeable (12.5%), and theknowledgeable good fraction (6.25%). The level of knowledge about the IUD at the age less than 35 years the majoritysufficiently , the level of knowledge about the IUD at the secondary level sufficient majority , the level of knowledge aboutlUDs inwomen who do notwork sufficient majority , and the level of knowledge about theIUD in primiparous mother sufficientmajority.